PENGELOLAAN KECELAKAAN PADA KAPAL - Prasetya Sigit Santosa (Majalah Ilmiah Bahari Jogja, 2018)
When the vessel sails at the sea, it cannot avoid the obstacles for example accidents or other emergency situations. Emergency situation is the situation when the ship is suddenly in an accident and it needs fast, accurate and integrated deterrence actions. Those actions include: preparation, practical management on handling the accident, and the solid organization. The preparation consists of the steps needed to handle a certain situation based on the types of the accidents, the practical management of a certain accident must be applied or followed, and the solid organization must have a clear communication and responsibility lines. There are two types of accident management/emergency procedure, namely: internal/local procedure and general procedure. Internal/local procedure is the guideline for executing in each division/department, in terms that the emergency situation can be handled by related division/department itself without interference from other vessels or port. General procedure is the comprehensive guideline issued by the company and includes the massive level of emergency situation or at least the happened accident will endanger other vessels or terminal at the port, and in terms of handling it needs a lot of people or involving other vessel and the authority of the port